Quantification of the Lateral Boundary Forcing of a Regional Climate Model Using an Aging Tracer - Lucas-Picher, Philippe; Caya, Daniel; Biner, Sébastien; Laprise, René (Monthly Weather Review, 2008)
Abstract The present work introduces a new and useful tool to quantify the lateral boundary forcing of a regional climate model (RCM). This tool, an aging tracer, computes the time the air parcels spend inside the limited-area domain of an RCM. The aging tracers are initialized to zero when the air parcels enter the domain and grow older during their migrations through the domain with each time step in the integration of the model. This technique was employed in a 10-member ensemble of 10-yr (1980–89) simulations with the Canadian RCM on a large domain covering North America. The residency time is treated and archived as the other simulated meteorological variables, therefore allowing computation of its climate diagnostics. These diagnostics show that the domain-averaged residency time is shorter in winter than in summer as a result of the faster winter atmospheric circulation. The residency time decreases with increasing height above the surface because of the faster atmospheric circulation at high levels dominated by the jet stream. Within the domain, the residency time increases from west to east according to the transportation of the aging tracer with the westerly general atmospheric circulation. A linear relation is found between the spatial distribution of the internal variability—computed with the variance between the ensemble members—and residency time. This relation indicates that the residency time can be used as a quantitative indicator to estimate the level of control exerted by the lateral boundary conditions on the RCM simulations.

Investigation of regional climate models’ internal variability with a ten-member ensemble of 10-year simulations over a large domain - Lucas-Picher, Philippe; Caya, Daniel; De Elía, Ramón; Laprise, René (Climate Dynamics, 2008)

Implementation of a large‐scale variable velocity river flow routing algorithm in the Canadian Regional Climate Model (CRCM) - Lucas‐Picher, Philippe; Arora, Vivek K.; Caya, Daniel; Laprise, René (Atmosphere-Ocean, 2003)

On the need for bias correction of regional climate change projections of temperature and precipitation - Christensen, Jens H.; Boberg, Fredrik; Christensen, Ole B.; Lucas‐Picher, Philippe (Geophysical Research Letters, 2008)
Within the framework of the European project ENSEMBLES (ensembles‐based predictions of climate changes and their impacts) we explore the systematic bias in simulated monthly mean temperature and precipitation for an ensemble of thirteen regional climate models (RCMs). The models have been forced with the European Centre for Medium Range Weather Forecasting Reanalysis (ERA40) and are compared to a new high resolution gridded observational data set. We find that each model has a distinct systematic bias relating both temperature and precipitation bias to the observed mean. By excluding the twenty‐five percent warmest and wettest months, respectively, we find that a derived second‐order fit from the remaining months can be used to estimate the values of the excluded months. We demonstrate that the common assumption of bias cancellation (invariance) in climate change projections can have significant limitations when temperatures in the warmest months exceed 4–6 °C above present day conditions.